The Formation of Domes in the Architectural Monuments of Central Asia - Khalikov Sindorkul Ravshanovich (Genius Journals, 2023)
This article describes the morphology, typology and history of the construction of domes of architectural monuments of Central Asia, the types of domes of architectural monuments of Uzbekistan, the originality of the artistic solutions of domes, the formation of domes in architectural monuments.
Keywords: Dome; Domemausoleum; monument